2021
DOI: 10.4236/crcm.2021.106020
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Hospital Lengths of Stay: A Five-Year Study

Abstract: Hospital length of stay reduction is an important mechanism for improving the outcomes and efficiency of care. This study evaluated the impact of length of stay reduction in the hospitals of Syracuse, New York. Between 2015 and 2020, length of stay reduction saved 7106 inpatient days for adult medicine, and 10,605 patient days for adult surgery in the hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…One study found a decreased risk of infection in patients with a decreased length of hospital stay (Odds ratio = 0.44) 48 . There is also available literature reporting the use of programs to shorten hospital stay saving over 6 million dollars in a 5‐year period, considering surgical patients in the United States 49 . All studies presented data that was in agreement with this finding.…”
Section: Discussionmentioning
confidence: 65%
“…One study found a decreased risk of infection in patients with a decreased length of hospital stay (Odds ratio = 0.44) 48 . There is also available literature reporting the use of programs to shorten hospital stay saving over 6 million dollars in a 5‐year period, considering surgical patients in the United States 49 . All studies presented data that was in agreement with this finding.…”
Section: Discussionmentioning
confidence: 65%
“…Although the determination as to the practical significance of a mean H-LOS reduction of .54 days is an entirely scientific/ medical one, it has been well established that reduction in H-LOS can lead to a reduction in health care costs and improved patient health outcomes. 30 As such, a reduction in H-LOS is a critical advantage of performing an appendectomy compared to keeping patients in the hospital to monitor response to antibiotic therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…32 Concurrently, efficiency gains have reduced the need for hospitalisation, hospital length of stay and cost of care. 33 Improved anaesthesia and surgical techniques have increased the capacity for day-case surgery, meaning in-patient admission has become reserved for patients with significant comorbidities and/or surgical complexity, who are at an increased risk of complications. The number and classes of available medications have increased, particularly around anticoagulants, immune modulators and cancer treatments (Table 2).…”
Section: Changes In Hospital Care and Workplace Requirements Since Rr...mentioning
confidence: 99%